这个主要利用两个公式
1+2+3+.....+n=n(n+1)/2
1^2+2^2+3^2+...+n^2=n(n+1)(2n+1)/6
1×2+2×3+3×4+4×5+…+n(n+1)
=(1^2+1)+(2^2+2)+(3^2+2)+...+(n^2+n)
=(1^2+2^2+...+n^2)+(1+2+3+....+n)
=n(n+1)(2n+1)/6+n(n+1)/2
=n(n+1)(n+2)
1×2×3+2×3×4+3×4×5+…+n(n+1)(n+2)=1/4×n(n+1)(n+2)(n+3)。
解答过程如下:
1×2×3+2×3×4+3×4×5+......+n(n+1)(n+2)
=1/4【1×2×3×4-0×1×2×3】+1/4【2×3×4×5-1×2×3×4】+1/4【3×4×5×6-2×3×4×5】+......+
1/4【n(n+1)(n+2)(n+3)-(n-1)n(n+1)(n+2)】
=1/4×n(n+1)(n+2)(n+3)
扩展资料:
相关公式:
(1)1+2+3+.+n=n(n+1)/2
(2)1^2+2^2+3^2+...+n^2=n(n+1)(2n+1)/6
(3)1×2+2×3+3×4+4×5+…+n(n+1)
=(1^2+1)+(2^2+2)+(3^2+2)+...+(n^2+n)
=(1^2+2^2+...+n^2)+(1+2+3+.+n)
=n(n+1)(2n+1)/6+n(n+1)/2
=n(n+1)(n+2)
This:1+2+3+.....+n=n(n+1)/2
1^2+2^2+3^2+...+n^2=n(n+1)(2n+1)/6
1×2+2×3+3×4+4×5+…+n(n+1)
=(1^2+1)+(2^2+2)+(3^2+2)+...+(n^2+n)
=(1^2+2^2+...+n^2)+(1+2+3+....+n)
=n(n+1)(2n+1)/6+n(n+1)/2
=n(n+1)(n+2)
Take It Easy